Definitive Chemoradiotherapy Compared to Neoadjuvant Chemoradiotherapy With Esophagectomy for Locoregional Esophageal Cancer: National Population-based Cohort Study. Issue 3 (March 2022) - Kamarajah, Sivesh K.; Phillips, Alexander W.; Hanna, George B.; Low, Donald; Markar, Sheraz R.
Abstract : Aim: Ongoing randomized controlled trials seek to evaluate the potential organ-preservation strategy of definitive chemoradiotherapy as a primary treatment for esophageal cancer. This population-based cohort study aimed to assess survival following definitive chemoradiotherapy (DCR) with or without salvage esophagectomy (SALV) in the treatment of esophageal cancer. Patients and Methods: Data from the National Cancer Database (NCDB) from 2004 to 2015, was used to identify patients with nonmetastatic esophageal cancer receiving either DCR (n = 5977) or neoadjuvant chemoradiotherapy with planned esophagectomy (NCRS) (n = 13, 555). Propensity score matching and multivariable analyses were used to account for treatment selection bias. Subset analyses compared patients receiving SALV after DCR with NCRS. Results: Comparison of baseline demographics of the unmatched cohort revealed that patients receiving NCRS were younger, had a lower burden of medical comorbidities, lower proportion of squamous cell carcinoma (SCC), and more positive lymph nodes. Following matching, NCRS was associated with significantly improved survival compared with DCR [hazard ratio (HR): 0.60, 95% confidence Interval (CI): 0.57–0.63, P < 0.001], which persisted in subset analyses of patients with adenocarcinoma (HR: 0.60, 95% CI: 0.56–0.63, P < 0.001) and SCC (HR: 0.58, 95% CI: 0.53–0.63, P < 0.001). Of 829 receiving SALV after DCR, 823 patients were matched to 1643 NCRS. There was no difference in overall survival between SALV and NCRS (HR: 1.00, 95% CI: 0.90–1.11, P = 1.0). Conclusions: Surgery remains an integral component of the management of patients with esophageal cancer. Neoadjuvant therapy followed by planned esophagectomy appears to remain the optimum curative treatment regime in patients with locoregional esophageal cancer. Abstract : Supplemental Digital Content is available in the text